A new electric wheel and optimization on its suspension parameters. (October 2020) - Meng, Lingsheng; Zou, Yuanji; Qin, Yudi; Hou, Zhichao
Hub-driven technology with its many advantages has become a potential transformation technology in the automotive industry. In order to inhibit the negative effects of the in-wheel motor, a new electric wheel configuration was presented with two-stage suspensions, and optimization was conducted for the suspension parameters. With the specially introduced flexible transmission elements and motor suspension, the electric wheel is capable of achieving power transmission and vertical vibration isolation simultaneously. A quarter-vehicle model was established, and vehicle performance-related indices were defined to evaluate the applicability of the new electric wheel. An optimization problem was then constructed for suspension parameters, where constraint conditions were derived according to vehicle dynamics. The optimal solution was sought by a genetic algorithm, aiming at utilizing the full potential of the configuration. Simulations were carried out taking the optimal suspension parameters into account, and comparison was made with vehicles equipped with other electric wheel configurations in terms of these performance indices. The results show that the proposed electric wheel reduces motor vibration, and increases wheel dynamic load and vehicle body acceleration.